Green Revolutions and Miracle Economies: Agricultural Innovation, Trade and Growth - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2005)
The purpose of this paper is to develop a simple model of an economy in which growth is driven by a combination of exogenous technical change in agriculture as well as by a rising world demand for labor-intensive manufactured exports. We explore the relative roles of agricultural innovation and rising export demand in a model with two traded industrial goods and a non-traded agricultural good, food. When the non-traded sector uses a specific factor, we show that technical change in agriculture may be the key to sustained factor accumulation in industry, in particular driving intersectoral labor migration. A key assumption is a less than unitary price elasticity of demand for food. Our results could form a crucial link in capturing the story of labor-abundant economies which experienced structural transformation and growth through labor-intensive manufactured exports, without prior technology breakthroughs in industry. They contribute to explaining the massive growth in factor accumulation which shows up in some growth accounting studies : they may also imply that some of the contribution of technical progress is mistakenly attributed solely to factor accumulation.